2015
DOI: 10.1371/journal.pone.0121616
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Visual Vertical and Postural Capability in Children Born Prematurely

Abstract: PurposeWe compared postural stability and subjective visual vertical performance in a group of very preterm-born children aged 3-4 years and in a group of age-matched full-term children.Materials and MethodsA platform (from TechnoConcept) was used to measure postural control in children. Perception of subjective visual vertical was also recorded with posture while the child had to adjust the vertical in the dark or with visual perturbation. Two other conditions (control conditions) were also recorded while the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 45 publications
(48 reference statements)
2
18
2
Order By: Relevance
“…We have suggested that the scarce subjective visual vertical performance we observed in younger children could have been due to immaturity of the cortical and central areas involved. This hypothesis is in line with the results of recent research conducted by our group (14,23), which explored the subjective visual vertical in healthy and preterm born children. More specifically, Gaertner et al (14) showed that the accuracy of verticality at six to eight years old was scarce because children in that study were more dependent on visual information, so that the poor estimation of the SVV may have been caused by imperfect or incomplete integration of visual information.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We have suggested that the scarce subjective visual vertical performance we observed in younger children could have been due to immaturity of the cortical and central areas involved. This hypothesis is in line with the results of recent research conducted by our group (14,23), which explored the subjective visual vertical in healthy and preterm born children. More specifically, Gaertner et al (14) showed that the accuracy of verticality at six to eight years old was scarce because children in that study were more dependent on visual information, so that the poor estimation of the SVV may have been caused by imperfect or incomplete integration of visual information.…”
Section: Discussionsupporting
confidence: 91%
“…More specifically, Gaertner et al (14) showed that the accuracy of verticality at six to eight years old was scarce because children in that study were more dependent on visual information, so that the poor estimation of the SVV may have been caused by imperfect or incomplete integration of visual information. Bucci et al (23), on the other hand, reported that preterm born children were more unstable than full-term born children and showed poor perceptions of verticality, probably due to the immaturity of the cortical processes involved in their motor control and in their treatment of perception and orientation of verticality.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that SVV and postural stability were impaired in preterm born children. [21] It is believed that SVV has a limited sensitivity for centrally compensated disease, however findings of the present study showed that there were SVV abnormalities in the long run. [1] When the perception of verticality fails, postural instability is the most common symptom, and it is also a significant factor for falling.…”
Section: Discussionmentioning
confidence: 49%
“…However, other studies have demonstrated similar findings at younger ages (Bucci et al, 2015;Burns et al, 1999;Lorefice et al, 2014;Lorefice et al, 2012a;Matiello & Woollacott, 1997). In a study of infants born between 26-33 weeks' gestational age, it was identified that at two years corrected age, infants who had bronchopulmonary dysplasia (also referred to as chronic neonatal lung disease) had significantly poorer postural control .…”
Section: Impact Of Preterm Birth On Postural Controlmentioning
confidence: 63%
“…When adjusting for growth, amongst children with a history of bronchopulmonary dysplasia, those whose weight was less than the 10th percentile demonstrated significant differences in postural control compared to those whose growth was within normal limits. More recently, Bucci et al confirmed that postural control at three to four years of age in children born very preterm (25-27 weeks' gestational age) is reduced compared to age-matched full-term peers (Bucci et al, 2015).…”
Section: Impact Of Preterm Birth On Postural Controlmentioning
confidence: 97%